Chromatin structure of the developmentally regulated early histone genes of the sea urchin Strongylocentrotus purpuratus. - Fronk, J (1990)
Chromatin organization of the early histone gene repeat was studied at the early embryonic stages of the sea urchin S. purpuratus. Micrococcal nuclease digestion showed a highly irregular packaging of the whole repeat at the period of transcriptional activity, which was progressively replaced by more regular nucleosomal arrays upon developmentally programmed inactivation. No evidence for unique positioning of the nucleosomes was found. Regions upstream of each of the genes were hypersensitive to DNAase I digestion in the active state. These regions contained one (H2A and H2B), or two (H3 and H4) well-defined DNAase I cutting sites, or two poorly-defined sites (H1). They mapped within DNA sequences shown previously to be required for proper expression of the genes. Hypersensitivity continued in the hatching blastula, which have a conventional nucleosomal structure and a much reduced transcriptional activity. Hypersensitivity of these regions during morula and early blastula was not dependent on the torsional strain in chromatin, as it was not influenced by extensive gamma ray-induced nicking of the DNA in nuclei. By late blastula no hypersensitive regions were present.